Insect Pests Diversity in Organic Edamame Cultivation with Application of Kiambang Bokashi - Untung Santoso; Noor Haina; Akhmad Rizali; Yulia Padma Sari (Warmadewa University Press, 2025)
Edamame soybean have a higher selling value compared to other soybeans and have good prospects. One of the inhibiting factors in edamame cultivation is pest infestation. Pest infestations can result in up to 80percentage loss of edamame crops. Plants that lack nutrients will be susceptible to pests. The application of bokashi kiambang fertilizer is one of the efforts to provide sufficient nutrients for edamame soybean plants. Calculation of insect pest diversity is very important to obtain information that can be used in making decisions on pest control measures. The purpose of this study was to determine the level of insect diversity in organic edamame cultivation used bokashi kiambang. This study used Randomized Block Design (RBD), with the treatment given being kiambang bokashi with five levels of treatment, namely 0 kg per plot, 2 kg per plot, 4 kg per plot, 6 kg per plot, and 8 kg per plot. The results of the study showed that the difference in the dose of bokashi kiambang had no effect on the diversity of insect pests. However, it can be known that the diversity index of insect pests has a status of moderate level of species diversity, the dominance index (C) of insect pests has a status of low dominance status to high, the equality index (E) of insect pests has a status of high level of population uniformity, and the type richness index (R) of insect pests has a status of low type richness level.